Surfactant-assisted immobilization of tio2 onto glass substrates for photocatalytic degradation of mathylene blue - Mariquit, E.G (ASEAN engineering journal)
Titanium dioxide-based photocatalysis is a type of advanced oxidation process that can be used to completely degrade and mineralize organic pollutants. The semiconductor titanium dioxide (TiO2)is used as a photocatalyst and is activated when it absorbs photon energy equal or greater than its band gap energy. The activation of TiO2 as a photocatalyst leads to the formation of active sites on its surface that can trigger series of oxidative-reductive reactions to mineralize the pollutants. In most cases, TiO2 is commonly used in slurry form and the recovery of the catalyst after water treatment often requires another separate process. To address this concern, TiO2 photocatalyst have been immobilized on the surface of soda borosilicate glass slides with the aid of a commercial non-ionic surfactant, under the trade name Triton X- 100. The TiO2 thin film was prepared using sol-gel process and immobilized on the glass surface at different number of coatings using the dip coating technique. The TiO2 thin films were characterized using FE-SEM, XRD and TGA and its photocatalytic activities were tested in the degradation of a model organic pollutant, methylene blue (MB). Characterization of the prepared samples by XRD showed that TiO2 in the form of anatase was successfully deposited on the glass slides. The addition of surfactant created thicker TiO2 thin films that showed better performance during photocatalytic activity test. The result of the activity tests showed that the TiO2 on the glass slide was able to degrade MB and the number of times that TiO2 was coated on the glass slide also affected the rate of MB degradation.